Assessment of Parent-Adolescent Communication about Sexual and Reproductive Health among High School Students in Mekelle Town, Northern Ethiopia (Global Journal of Medical Research, 2016)
Abstract not found
Keywords: adolescent; parent; communication; sexual; reproductive; health; northern ethiopia